1996
DOI: 10.1002/anie.199623861
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Recognition of Chiral Carbamoyl‐α‐Hydroxyacids with a Cleft‐Type Receptor

Abstract: gen bonds with an a-functionalized carboxylic acid as the guest 6 , = 5.21 6,, = 0.69 / ( 9 -5 (4-1 P.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Knowing the cation−crown ether 2 −tosylate stability constants, we were able to determine the K a of the corresponding BTMA + complex by an alternative method, namely by competitive NMR titrations . For this, increasing amounts of BTMA + iodide were added to solutions of, e.g., K + −18-crown-6 2 −tosylate in CDCl 3 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Knowing the cation−crown ether 2 −tosylate stability constants, we were able to determine the K a of the corresponding BTMA + complex by an alternative method, namely by competitive NMR titrations . For this, increasing amounts of BTMA + iodide were added to solutions of, e.g., K + −18-crown-6 2 −tosylate in CDCl 3 .…”
Section: Resultsmentioning
confidence: 99%
“…In all dilution titrations, the dissociation of the cationcrown ether complexes at low concentrations was taken into (18) Molecular modeling was performed on a Silicon Graphics workstation using the program Cerius 2 (Molecular Simulations Inc.) with a Dreiding 2. 21 account by including the corresponding stability constants 20 in the calculations. With Li + and 12-crown-4, the upfield shift upon complexation by 2-tosylate was not large enough to be followed quantitatively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These promising results suggested that it might be possible to resolve a racemic mixture of host 2, using its supramolecular properties. 3 Ethoxycarbonyl--leucine was selected as the guest due to its lack of UV absorption at 250 nm. Preparative TLCs were impregnated with a 2% amino acid solution in chloroform, dried and loaded with host 2 (50 mg); elution with CH 2 Cl 2 resulted in two different bands (R f = 0.72, R f = 0.23) for each of host 2 enantiomers.…”
Section: Perkinmentioning
confidence: 99%
“…Very high values of enantioselectivity can be attained with specific selectors for particular enantiomers [182,[201][202][203][204]. Nevertheless, the application domain is reduced consequently.…”
Section: Global Considerationsmentioning
confidence: 99%